Fabrication of a Motor Vehicle Ignition System Simulation Tool - Nur Adnan Wiraendra; Irfan maulana (Jurnal Inovasi Mesin, 2025)
The rapid development of technology has had a significant impact on innovations in learning media within the field of education, including practical activities conducted in the Thermal Laboratory of Politeknik Negeri Bandung. Learning about thermal engines, particularly gasoline engines, requires a thorough understanding of how the ignition system works. Until now, students have only received explanations through theory or videos, resulting in limited comprehension and insufficient stimulation for the development of practical skills. This study aims to develop a learning media in the form of an ignition system simulation tool for motor vehicles. This tool allows students to directly observe the ignition process, thereby enhancing their understanding and analytical abilities regarding the performance of the ignition system. The simulation tool was created using a DC motor as a substitute for engine rotation. The process of fabricating this simulation tool includes several stages, namely needs analysis, design, fabrication, and testing. The test results indicate that the DC motor in this simulation tool is capable of producing a maximum rotational speed of 3100 RPM, with a power requirement of 12 V and a current of 2 A. The spark produced at the spark plug appears blue and clearly visible, indicating that the tool can function optimally as an interactive learning media.